Un concepto alternativo del derecho El derecho como generalización de complejos normativos - Rodriguez Gaona, Roberto (Ciencia Huasteca Boletín Científico de la Escuela Superior de Huejutla, 2018)
This paper presents an alternative concept of law that considers it as a generalization of normative complex. It claims that one must differentiate from a political structure and law itself. It is explained that it exists an special rule called rule of vectura that allows transport of norms and rules to a legal system of a political structure.